Participation in Budgeting and Motivation on Employee Performance - Tiomy B Adi (Yayasan Pendidikan Bukhari Dwi Muslim, 2022)
The purpose of this study was to determine and analyze the effect of participation in budgeting and motivation on employee performance at Weda Hospital, Central Halmahera. The population in this study were all employees who worked at Weda Hospital, Central Halmahera, amounting to 72 people. To determine the sample in this study, the study used non-probability sampling, with a convenience sampling technique. The data used in this study is primary data collected by distributing questionnaires to all respondents. This study uses quantitative analysis using a simple linear regression model, namely by performing the t-test and F-test. The process of processing and calculating data using the SPSS application. The results showed that the participation variable in budgeting had a positive effect on employee performance at Weda Hospital, Central Halmahera. This means that if participation in budgeting increases, it will increase employee performance. While the motivation variable has a negative effect on employee performance. This means that if motivation increases, employee performance will decrease, this means that employees feel that giving motivation at Weda Halmahera Hospital cannot provide encouragement or enthusiasm for their workers